<span>h(x)=4x2−7x−17
a get like this:
</span>h(x)=f(x)−g(x) =6x2−3x−9-(2x2+4x+8)=6x2−3x−9-2x2-4x-8=4x2−7x−17
Answer:
JL = 78
Step-by-step explanation:
MN is a midsegment. Based on the midsegment theorem,
MN = ½(JL)
MN = 5x - 16
JL = 4x + 34
Plug in the value
5x - 16 = ½(4x + 34)
5x - 16 = ½*4x + ½*34
5x - 16 = 2x + 17
Collect like terms
5x - 2x = 16 + 17
3x = 33
Divide both sides by 3
x = 11
✔️JL = 4x + 34
Plug in the value of x
JL = 4(11) + 34
JL = 44 + 34
JL = 78
Answer:
13
Step-by-step explanation:
We know that a^2+b^2 = c^2 where a and b are the legs and c is the hypotenuse
5^2 + 12^2 = c^2
25+144 = c^2
169 = c^2
Taking the square root of each side
sqrt(169) = sqrt(c^2)
13 =c
A because we all know the intersection of sin is always in (0,0) but in this case it is different
Step-by-step explanation:
.......................................................... (2×3)+(6×3)